The Effect of Using Local Microorganism of Rument Contents and Crude Enzymes with Different Dosage on The Nutrient Content of Oil Palm Frond - Tri Astuti; Syahro Akbar; Harissatria Harissatria; Rica M. Sari; Delsi Afriani; Nasir Ropiq (Hasanuddin Journal of Animal Science (HAJAS), 2021)
This study aims to evaluate the dry matter, organic matter, and crude protein content of palm oil fronds incubated with local microorganism source of rumen content and crude enzymes produced through the rumen of cattle. The rumen contents of the beef were incubated for 7 days with a fermented system in the rumen with the addition of molasses and soybean soaking water as a source of food and energy, as well as the addition of palm fronds as a source of lignin enzymes. The design used was factorial completely randomized design 2 X 3 with 3 replications for each treatment. Factor A consisted of two treatments, there were: A1 = Local microorganism source of rumen content of beef, A2 = crude enzyme. Factor B using of dose: B1 = 10%, B2 = 20%, B3 = 30%. The parameters observed were: dry matter content, organic matter, crude protein.  The resulted were 33.11-34.75% the content of dry matter, 93.40-93.08% the content of organic matter, and the content of crude protein based on this research data, it can be concluded that the incubation treatment of oil palm fronds with local microorganisms (Mol) and crude enzymes affects the dry matter and organic matter content. Crude protein content ranged from 6.70 to 7.38%.